Elite male flat jockeys display lower bone density and lower resting metabolic rate than their female counterparts: implications for athlete welfare - Wilson, G.; Hill, J.; Sale, C.; Morton, J. P.; Close, G. L. (Applied Physiology, Nutrition, and Metabolism, 2015)
To test the hypothesis that daily weight-making is more problematic to health in male compared with female jockeys, we compared the bone density and resting metabolic rate (RMR) in weight-matched male and female Flat jockeys. RMR (kcal/kg lean mass) was lower in males compared with females as well as lower bone-density Z scores at the hip and lumbar spine. Data suggest the lifestyle of male jockeys compromise health more severely than females, possibly because of making weight more frequently.